2016
DOI: 10.1016/j.diii.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of Schmorl's nodes: Imaging characteristics and epidemio-clinical relationships

Abstract: Our study suggests a potential role for ethnical and physical factors in the pathogenesis of SN. Furthers studies are mandatory to evaluate their clinical relevance, especially in patients such as Caucasian manual workers in whom SN have a high prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The prevalence of SN was significantly increased as age advanced, comparable with previous studies that suggested weakened aged cartilaginous endplates and reduced bone density in older age groups; both factors may play a role in pathogenesis of SNs [25][26][27]. The higher lumber levels were affected more, as L1-L2 was the most affected disc (23.6%) in the current study; this was consistent with most of the papers [8,24,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of SN was significantly increased as age advanced, comparable with previous studies that suggested weakened aged cartilaginous endplates and reduced bone density in older age groups; both factors may play a role in pathogenesis of SNs [25][26][27]. The higher lumber levels were affected more, as L1-L2 was the most affected disc (23.6%) in the current study; this was consistent with most of the papers [8,24,27].…”
Section: Discussionsupporting
confidence: 91%
“…According to this paper, we prefer the theory of endplate osteonecrosis as a cause of SNs, rather than disc degeneration, as a study examined the surgical specimens of SNs proposed that the SNs are the end result of ischemic death of bone beneath the endplate and the herniation of the disc into the body of the vertebra is a secondary phenomenon. The hypothesis of microtrauma is also preferred as Burke et al found more SN in American soldiers [26]; these minor traumas cause herniation of nucleus pulposus through developmental weak points in the endplates [28]. Also, the developmental models revealed that SNs are already present during skeletal maturation prior the beginning of degeneration [2].…”
Section: Discussionmentioning
confidence: 99%
“…MRI also shows the shape of IVDs and vertebrae clearly and is commonly used for recording Schmorl's nodes. 19 The prevalence of some MRI findings (eg, Modic changes and spinal canal stenosis) was low, excluding any prominent differences between the groups. The inter-rater disagreement in IVD degeneration is endorsed by the fact that the Pfirrmann classification is primarily structured for and used in the assessment of lumbar IVDs, but it has been adapted also in assessment of cervical spine.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 88%
“…Schmorl nodes correspond to herniation of nucleus material through the endplate of the vertebral bodies into the subchondral bone (28).…”
Section: Schmorl Nodesmentioning
confidence: 99%